Praktik Analisis Swot Dalam Strategi Pemasaran Syariah Produk Tabungan Ib Hijrah Prima Pt Bank Muamalat Indonesia Tbk Kcp Genteng - Munawir, Munawir; Aziziy, Riza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to find out the sharia marketing strategy for iB Hijrah Prima Savings products at PT Bank Muamalat Indonesia Tbk, KCP Genteng and how to SWOT analysis in the marketing strategy for iB Hijrah Prima Savings products at PT. Bank Muamalat Indonesia Tbk, KCP Genteng. This study uses qualitative research. The results of the study show that the strategy used by PT Bank Muamalat Indonesia Tbk, KCP Genteng to promote the iB Hijrah Prima savings product is by means of promotion and approach to customers who are already the target of Bank Muamalat. In the SWOT Analysis strategy, Bank Muamalat has great strengths and opportunities to promote iB Hijrah Prima savings products. Marketing strategy in promoting iB Hijrah Prima savings products through promotions and approaches to customers. The SWOT analysis in promoting iB Hijrah Prima savings has very good strengths and opportunities.